OSAKA trial: a randomized, controlled trial comparing tacrolimus QD and BD in kidney transplantation - Albano, Laetitia; Banas, Bernhard; Klempnauer, Juergen L; Glyda, Maciej; Viklicky, Ondrej; Kamar, Nassim; Optimising immunoSuppression After Kidney transplantation with ADVAGRAF Study Group (Transplantation, 2013)
BACKGROUND: The once-daily (QD), prolonged-release formulation of tacrolimus has been shown to improve adherence versus twice-daily (BD) tacrolimus. Treatment nonadherence in transplant recipients has been associated with poor graft outcomes. METHODS: This open-label, parallel-group study randomized adults with end-stage renal disease undergoing primary kidney transplantation or retransplantation to an initial dose of tacrolimus BD 0.2 mg/kg per day (Arm 1; n=309), QD 0.2 mg/kg per day (Arm 2; n=302), QD 0.3 mg/kg per day (Arm 3; n=304) all with mycophenolate mofetil and corticosteroids (tapered) over 24 weeks, or tacrolimus QD 0.2 mg/kg per day with mycophenolate mofetil, basiliximab, and corticosteroids given only perioperatively (Arm 4; n=283). The primary composite endpoint (efficacy failure; per protocol set) was defined as graft loss, biopsy-confirmed acute rejection, or graft dysfunction at week 24. Graft dysfunction was defined as estimated glomerular filtration rate Modification of Diet in Renal Disease-4 formula of less than 40 mL/min/1.73 m(2). The prespecified noninferiority margin was 12.5%. RESULTS: The per protocol set included 976 patients: 237, 263, 246, and 230 patients in Arms 1 to 4, respectively. Noninferiority of the composite endpoint was demonstrated for Arm 2 versus Arm 1; Kaplan-Meier estimates of efficacy failure were 42.2% and 40.6%, respectively (difference, -1.6%; 95% confidence interval [CI], -12.2% to 9.0%). Noninferiority to Arm 1 was not confirmed for Arm 3 (difference, -3.5%; 95% CI, -13.6% to 6.6%) or Arm 4 (difference, -7.1%; 95% CI, -16.1% to 1.9%). Graft dysfunction (estimated glomerular filtration rate <40 mL/min/1.73 m(2)) was the main determinant of composite-endpoint efficacy failure across all arms. CONCLUSIONS: In patients representative of the European kidney transplant population, tacrolimus QD-based immunosuppression (0.2 mg/kg/day), without induction, showed similar efficacy to 0.2 mg/kg per day tacrolimus BD.
Keywords: Kidney Failure, Chronic; Biopsy; Humans; lidé středního věku; Drug Administration Schedule; Graft Rejection; Dose-Response Relationship, Drug; Female; dospělí; výsledek terapie; lidé; imunosupresiva; biopsie; Adult; Immunosuppressive Agents; transplantace ledvin; ženské pohlaví; chronické selhání ledvin; Male; Middle Aged; Treatment Outcome; Tacrolimus; Kidney Transplantation; vztah mezi dávkou a účinkem léčiva; takrolimus; mužské pohlaví; rozvrh dávkování léků; rejekce štěpu